Safety and accuracy of core biopsy in retroperitoneal sarcomas. Issue 1 (31st October 2013) - Hwang, Sang Yun; Warrier, Sanjay; Thompson, Stephen; Davidson, Trent; Yang, Jia Lin; Crowe, Philip
Abstract: Aim: Retroperitoneal sarcomas (RPSs) are large, rare tumors. The role of core biopsy for retroperitoneal masses identified by preoperative imaging is unclear and we report the safety and accuracy of core biopsies at a specialized sarcoma unit in Sydney, Australia. Methods: A retrospective analysis of a prospectively collected database was performed to identify the safety and accuracy of core biopsies in patients who were confirmed to have RPS. Results: Twenty‐two patients underwent biopsies with no recorded morbidity or tumor seeding. RPS was correctly identified in 82%. Median follow‐up was 19 months. Conclusion: We demonstrate that core biopsy is safe and can identify RPSs.